The Development of Smart Card-Based Media on the Beauty of Togetherness Themes in Class IV Elementary School of 026609, South Binjai District - Thessa Herdyana (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research is aimed to describe the development of smart card based media on the beauty of togetherness themes in class IV elementary school of 026609, South Binjai District. This research was carried out in stages from December to March. The subjects of this research were fourth grade students in elementary school of 026609, South Binjai District by taking as many as 28 students as a large group trial and 10 students for a small group trial. The object of the research is the smart card-based media which developed. This research found that the effectiveness of smart card-based media in improving student learning outcomes has been effectively used in learning, this can be seen from the results of the completeness of student learning in a classical manner on trial I or small group that obtained percentage of 90% and 76% of student response questionnaire and in trial II or large groups of learning outcomes is obtained a percentage of 86% and the results of student response questionnaire is obtained to 86.23%.